2021
DOI: 10.3389/fcell.2021.662711
|View full text |Cite
|
Sign up to set email alerts
|

The Road Less Traveled? Unconventional Protein Secretion at Parasite–Host Interfaces

Abstract: Protein secretion in eukaryotic cells is a well-studied process, which has been known for decades and is dealt with by any standard cell biology textbook. However, over the past 20 years, several studies led to the realization that protein secretion as a process might not be as uniform among different cargos as once thought. While in classic canonical secretion proteins carry a signal sequence, the secretory or surface proteome of several organisms demonstrated a lack of such signals in several secreted protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 134 publications
0
23
0
Order By: Relevance
“…It is worth mentioning that the vast majority of the reported proteins have been described as having other canonical functions, apart from their participation in the manipulation of the host haemostatic system. This mechanism is referred to as "moonlighting" and constitutes an advantageous parasite strategy of energy saving based on proteins exhibiting "expected or unexpected" functions depending on some factors, such as their different location or secretory pathways [7,26]. In line with this, our results showed that the majority of the interactions were described in surface parasitic extracts and excretory/secretory products, which indicates that parasite molecules involved in the exploitation of the host haemostatic system are mainly expressed on the parasite surface or secreted to their environment from the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the vast majority of the reported proteins have been described as having other canonical functions, apart from their participation in the manipulation of the host haemostatic system. This mechanism is referred to as "moonlighting" and constitutes an advantageous parasite strategy of energy saving based on proteins exhibiting "expected or unexpected" functions depending on some factors, such as their different location or secretory pathways [7,26]. In line with this, our results showed that the majority of the interactions were described in surface parasitic extracts and excretory/secretory products, which indicates that parasite molecules involved in the exploitation of the host haemostatic system are mainly expressed on the parasite surface or secreted to their environment from the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…In Leishmania , 98% of the secreted proteins lack SP, suggesting the presence of other secretion pathways ( Silverman et al., 2008 ). The second mechanism is unconventional protein secretion (UPS) and refers to proteins either exposed on the cell surface or in the extracellular medium ( Balmer and Faso, 2021 ). The third mechanism is through extracellular vesicles (EVs), lipid-bound vesicles which either bud from the plasma membrane (microvesicles) or are derived from multivesicular bodies that fuse with the plasma membrane (exosomes) ( Dlugonska and Gatkowska, 2016 ; Mathieu et al., 2019 ; Babatunde et al., 2020 ) and for more details in mechanisms of secretion see ( Teng and Fussenegger, 2021 ).…”
Section: Mechanisms Of Parasite Effector Release/secretionmentioning
confidence: 99%
“…Moreover, the translocation of GAPDH to the nucleus in response to cellular stress is evidence of GAPDH involvement in nonmetabolic processes in higher eukaryotic cells [49]. When these Leishmania cells were exposed to cellular stress, such as serum withdrawal or stress generated by hydrogen peroxide exposure, no translocation of GFP-cGAPDH fusion proteins into the nucleus was observed.…”
Section: Purine Salvage Pathwaymentioning
confidence: 99%